Peran Pembelajaran Organisasi Dalam Mengatasi Persepsi Negatif Konsumen Di Era Digital (Studi Kasus Eiger) - Hilma Harmen; Erwin Nardo Sinaga; Alisya Adelia; Sonya Lalla Saragih; Greace Masrouli Malau; Putri Ananda (CV. ITTC INDONESIA, 2025)
The evolution of the digital era has transformed organizational communication paradigms, where the rapid dissemination of information through social media can trigger reputational crises from even minor communication errors. The case of PT Eigerindo Multi Produk Industri (Eiger) illustrates how negative consumer perceptions can escalate widely due to the volatile nature of digital interactions. This study aims to analyze the role of organizational learning in addressing negative consumer perceptions in the digital era through a case study of Eiger. The research employs a qualitative descriptive method based on literature review, with data collected from academic sources, news articles, and company documents. The findings reveal that organizational learning, particularly through double-loop learning, enables the company to critically reflect on communication failures, reassess internal values, and develop more adaptive, transparent, and consumer-oriented digital communication strategies. These results highlight that organizational learning functions not only as a mechanism for reputation recovery but also as a foundation for fostering a resilient and reflective corporate culture. The study implies that continuous application of organizational learning can strengthen resilience, enhance credibility, and rebuild long-term consumer trust amidst the growing complexity of digital communication dynamics.